Global burden of hypertensive heart disease attributable to high body mass index from 1990 to 2021: a multidimensional analysis and public health response - Sun, Zhenhai; Zhang, Rui; Cong, Mingyang; Zhang, Menghe; Lv, Tailong; Xie, Huidan; Chen, Shouqiang (Frontiers in Cardiovascular Medicine, 2025)
BackgroundAs the global population of obese individuals surpasses 878 million, the impact of high body mass index (BMI) on hypertensive heart disease (HHD) has risen to the third position among all diseases. However, the specific contribution of high BMI to the burden of HHD remains unclear.MethodsData on deaths, disability-adjusted life years (DALYs), and their age-standardized rates (ASR) were obtained from the Global Burden of Disease (GBD) database. Population attributable fractions (PAF) was used to assess the contribution of risk factors. Various analytical methods, including decomposition analysis, cluster analysis, frontier analysis, age-period-cohort (APC) analysis, and Bayesian age-period-cohort (BAPC) analysis, were employed to investigate changes in disease burden.ResultsThe results showed an increasing global burden of HHD due to high BMI, with both mortality and DALYs doubling over the past 30 years. Their ASR also continued to rise. By 2021, the PAF for deaths and DALYs reached 44% and 49%, respectively. Population growth and aging were significant contributors to this disease burden. Low- and middle- Socio-Demographic Index (SDI) regions experienced the highest burden, particularly in East Asia, South Asia, North Africa and Middle East. Although the disease burden was lower in high-income areas, the increase was notable, especially in North America. Women and older populations faced higher risks, particularly alarming is the rapid increase in risk among younger populations in high SDI regions.ConclusionHHD resulting from high BMI poses a significant global public health challenge, particularly in regions with middle and low SDI. While the heightened risk among women and older individuals has garnered considerable attention, the increasing risk among younger populations also necessitates greater focus. Targeted interventions should prioritize diet, exercise, medical security, and health education, with particular emphasis on enhancing policy support for low-income and high-risk groups. Future policies must integrate the social, economic, and cultural contexts of each region, implement comprehensive prevention and control strategies, and establish a multi-dimensional health promotion system.